Comprehensive insights into the combinatorial uses of selected phytochemicals in colorectal cancer prevention and treatment: isothiocyanates, quinones, carotenoids, and alkaloids - Deng, Xi; Yang, Zhongming; Han, Mingzhao; Ismail, Norsharina; Mohd Esa, Norhaizan; Abdull Razis, Ahmad Faizal; Abu Bakar, Md Zuki; Chan, Kim Wei (John Wiley and Sons, 2024)
Despite the advancement in cancer diagnosis and treatment, colorectal cancer remains the leading cause of cancer-related death worldwide. Given the high recurrence rate of colorectal cancer even after surgical resection, chemotherapy has been clinically used to improve the treatment outcomes of colorectal cancer. However, chemotherapy is well-known for its toxic side effects. Thus, phytochemicals have been widely studied in recent years as preventive and therapeutic agents for colorectal cancer owing to their relatively low toxicity. Moreover, combinatorial uses of phytochemicals with other natural compounds or with drugs may amplify the positive outcomes of colorectal cancer prevention and treatment by intervening in multiple signaling pathways and targets. This review summarized the combinatorial use of several well-studied groups of phytochemicals, that is, isothiocyanates, quinones, carotenoids, and alkaloids, in the prevention and treatment of colorectal cancer, and suggested it as a potential approach to improve the anticancer efficacy of single compounds and minimize the toxic side effects associated with conventional drugs. Notably, we generalized the in vitro, in vivo, and clinical experiments-based molecular mechanisms whereby the selected phytochemicals in combination with other compounds exerted anti-colorectal cancer effects by inhibiting cancer cell proliferation, cell apoptosis, cell invasion, and tumor growth. Overall, this review provides a reference and new perspective to propel further advancements in research and development of preventative and therapeutic strategies for colorectal cancer.